2010
DOI: 10.1016/j.jhe.2010.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic risk, market risk and correlation dynamics in the US real estate investment trusts

Abstract: a b s t r a c tThis study examines total, market and idiosyncratic risk and correlation dynamics using weekly return data on two US REIT firm samples from 1988 to 2008. We find that both market and idiosyncratic variance are time-varying and that idiosyncratic variance represents a dominant component of a REIT firm's total variance. We find a decline in idiosyncratic risk as well as a rise in average REIT correlation during the new REIT era, from 1993 to 2008. This recent downward trend of idiosyncratic risk a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
3
9
2
Order By: Relevance
“…While the inclusion increases the average adjusted R 2 substantially, neither realised nor idiosyncratic volatility seems to be unconditionally priced in the cross-section of real estate equity returns. This result is in contrast to Chiang et al (2009), Ooi et al (2009), Liow and Addae-Dappah (2010 and DeLisle et al (2011), who show that idiosyncratic volatility is either positively or negatively priced in the cross-section of US REIT returns. However, the results support the conception of the modern portfolio theory and the CAPM in that idiosyncratic risk is diversifiable and that an investor should not be rewarded for being exposed to avoidable risk.…”
Section: Idiosyncratic Riskcontrasting
confidence: 95%
See 1 more Smart Citation
“…While the inclusion increases the average adjusted R 2 substantially, neither realised nor idiosyncratic volatility seems to be unconditionally priced in the cross-section of real estate equity returns. This result is in contrast to Chiang et al (2009), Ooi et al (2009), Liow and Addae-Dappah (2010 and DeLisle et al (2011), who show that idiosyncratic volatility is either positively or negatively priced in the cross-section of US REIT returns. However, the results support the conception of the modern portfolio theory and the CAPM in that idiosyncratic risk is diversifiable and that an investor should not be rewarded for being exposed to avoidable risk.…”
Section: Idiosyncratic Riskcontrasting
confidence: 95%
“…Depending on the return frequency used to calculate idiosyncratic risk (daily vs monthly), portfolio or individual stock level data, return weighting procedures, idiosyncratic volatility measures and general model set-up, idiosyncratic risk is found to be either positively, negatively or unrelated to expected stock returns. Concerning the US-REIT market, the studies of Jirasakuldech et al (2009), Chiang et al (2009), Ooi et al (2009), Liow and Addae-Dappah (2010) and DeLisle et al (2011) add to the inconclusive evidence on the pricing of idiosyncratic risk.…”
Section: Introductionmentioning
confidence: 99%
“…Idiosyncratic risk is important for real estate as investors tend to hold small undiversified portfolios due to the localized and segmented nature of the asset. Clayton and MacKinnon () find that idiosyncratic risk for REITs is large and increasing over time, although Liow and Addae‐Dapaah () note that the recent trend is downwards. REITs have low beta exposures, but this varies across assets and time (Khoo, Hartzell and Hoesli ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, people find that idiosyncratic risk cannot be entirely removed by diversification in real markets, especially in the property market. Some evidence shows that idiosyncratic risk plays a significant role in explaining the excess risk premium (Liow & Addae-Dapaah, 2010). Leverage and illiquidity, as important characteristics of real estate investment, are responsible for undiversifiable risk.…”
Section: Introductionmentioning
confidence: 99%
“…This paper attempts to examine the spillover effect of idiosyncratic risk in REIT returns to explore the material implications for asset pricing and make a contribution to the knowledge. In addition, many studies have revealed that idiosyncratic risk is a time-varying attribute in REIT markets along with financial fluctuations (Liow & Addae-Dapaah, 2010). In general, the time-varying behaviour of volatility indicates the importance of the diversification of portfolio management at different stages of the of idiosyncratic risk and its spillover with REIT returns; and iii) establishing an asymmetric model to analyse the asymmetric responses of volatility terms.…”
Section: Introductionmentioning
confidence: 99%